2018
DOI: 10.1098/rspb.2018.0948
|View full text |Cite
|
Sign up to set email alerts
|

Bottlenose dolphins can understand their partner's role in a cooperative task

Abstract: In recent decades, a number of studies have examined whether various non-human animals understand their partner's role in cooperative situations. Yet the relatively tolerant timing requirements of these tasks make it theoretically possible for animals to succeed by using simple behavioural strategies rather than by jointly intended coordination. Here we investigated whether bottlenose dolphins could understand a cooperative partner's role by testing whether they could learn a button-pressing task requiring pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 49 publications
0
55
2
Order By: Relevance
“…This demonstration agreed with other studies that recorded similar cooperative rope‐pulling tasks in other socially complex mammal species such as orangutans (Chalmeau, Lardeux, Brandibas, & Gallo, 1997), chimpanzees (Melis, Hare, & Tomasello, 2006), spotted hyenas (Drea & Carter, 2009), or Asian elephants (Plotnik, Lair, Suphachoksahakun, & de Waal, 2011). Unlike the gradually introduced partner delay used by Plotnik et al (2011) or Jaakkola et al (2018), Domino was not shaped toward the delayed partner situation. The 30‐s delay was introduced in one step.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…This demonstration agreed with other studies that recorded similar cooperative rope‐pulling tasks in other socially complex mammal species such as orangutans (Chalmeau, Lardeux, Brandibas, & Gallo, 1997), chimpanzees (Melis, Hare, & Tomasello, 2006), spotted hyenas (Drea & Carter, 2009), or Asian elephants (Plotnik, Lair, Suphachoksahakun, & de Waal, 2011). Unlike the gradually introduced partner delay used by Plotnik et al (2011) or Jaakkola et al (2018), Domino was not shaped toward the delayed partner situation. The 30‐s delay was introduced in one step.…”
Section: Discussioncontrasting
confidence: 60%
“…Recent studies have examined dolphin cooperation (Eskelinen, Winship, Jones, Ames, & Kuczaj, 2016; Jaakkola, Guarino, Donegan, & King, 2018; Kuczaj, Winship, & Eskelinen, 2015). Kuczaj et al, (2015) introduced an apparatus to a group of six dolphins under human care that contained fish and ice reinforcement and was designed to be manipulated by pairs of dolphins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We caution that both mutual motor imitation and entrainment involve movement prediction so the relationship between the two phenomena remains to be clarified. The work of Herman (2002) on novel synchronous behavior and Jaakkola, Guarino, Donegan, and King (2018) on cooperation demonstrate that studies examining dolphin synchrony using the mirror game paradigm, particularly comparing their performance in the joint imitation versus follow‐the‐leader protocols, are eminently practical.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of cooperation and the cognitive abilities required for cooperation can be categorized into four types: recognition of the other’s presence; recognition of the other’s particular action; adjusting actions to those of others in time, space, or both; and adjusting actions as a result of understanding the other’s role (Albiach-Serrano, 2015). To examine the degree to which animals understand a cooperative task, experimental studies have been conducted using a task where two individuals need to simultaneously pull a rope or handles or push buttons (Crawford, 1937; Hirata & Fuwa, 2007; Jaakkola et al, 2018). Previous studies have suggested that the necessity of a partner to solve the cooperative task was understood by chimpanzees (Chalmeau, 1994; Hirata & Fuwa, 2007), orangutans ( Pongo pygmaeus : Chalmeau et al, 1997), capuchin monkeys ( Cebus apella : Mendres & De Waal, 2000), Asian elephants ( Elephas maximus : Plotnik et al, 2011), wolves ( Canis lupus : Marshall-Pescini et al, 2017), dogs ( Canis familiaris : Ostojić & Clayton, 2014), and spotted hyenas ( Crocuta crocuta : Drea & Carter, 2009), because they were more likely to perform the task in the presence of a partner, glance at the partner during the task, and wait for the arrival of a partner, and/or they were less likely to succeed at the task when the visual cues were blocked.…”
Section: Introductionmentioning
confidence: 99%